Loss of buoyancy control following a pneumonectomy: an update on Keeling syndrome with a biomechanics-based explanation. (7th September 2018) - Tsagkari, Eleni; Kapetanakis, Emmanouil I; Goutis, Georgios; Tomos, Periklis
Abstract: Pneumonectomy although nowadays less prevalent, still remains a viable, practiced lung resection for the treatment of lung cancer and other lung pathologies. However, as radical surgery, it is associated with a number of postoperative complications and possible sequela. One such unusual complication discovered is the loss of buoyancy control and the ability to float and swim when compared preoperatively. We report on 2 post-pneumonectomy patients who experienced significant instability and loss of buoyancy when they attempted to resume recreational swimming and offer a possible biomechanics-based explanation for this.